The causes, consequences and remedies of deforestation in Ethiopia - Alemayehu Oljirra (Brawijaya University, 2019)
Forests are one of the most valuable ecosystems in the world, containing over 60% of the world’s biodiversity. This ecosystem has multiple social economic values, apart from its intrinsic value. Forest provides a sustainable environment. Deforestation leads to the disappearance of sustainable development. Deforestation takes place due to multiple of reasons like logging, population growth, urbanization, grazing, construction of dams and reservoirs, habitat fragmentation, slash and burn method of farming, wildfire, global warming, hydroelectric projects. Agriculture is considered to be the backbone of the Ethiopian economy and almost 85% of the societies in Ethiopia engage in agriculture. The agricultural sector in Ethiopia in particular and in Africa, in general, is highly affected by deforestation directly and indirectly. Therefore, this paper focuses not only on the causes and consequences of deforestation but also seeks for better alternatives to tackle deforestation in Ethiopia